DETERMINAN OPINI AUDIT GOING CONCERN (Studi Empiris Pada Perusahaan Real Estate dan Property yang Terdaftar di BEI Tahun 2013-2015) - Hafid Byusi; Fatchan Achyani (Universitas Muhammadiyah Surakarta, 2018)
AbstractThis research aims to analyze the influence of opinion shopping, corporate growth, liquidity, the proportion of independent commissioners and audit committee on acceptance of going concern audit opinion. The populations in this research are real estate and property companies listed in Indonesia Stock Exchange. Sampling was done by purposive sampling method and obtained 120 companies as a sample for the period 2013-2015. Data analysis technique used logistic regression analysis. The results of this research prove that liquidity has a significant effect on the acceptance of going concern audit opinion, while opinion shopping, company growth, the proportion of independent commissioners, and audit committee have no significant effect on the acceptance of going concern audit opinion.Keywords: opinion shopping, company growth, liquidity, the proportion of independent commissioners, audit committee, going concern audit opinion.